2012
DOI: 10.3233/jhd-2012-120009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differences Between Direct and Indirect Striatal Output Pathways in Huntington's Disease

Abstract: There is morphological evidence for differential alterations in striatal medium-sized spiny neurons (MSNs) giving rise to the direct and indirect output pathways in Huntington's disease (HD). MSNs of the indirect pathway appear to be particularly vulnerable and markers for these neurons are lost early in postmortem brains and in genetic mouse models. In contrast, MSNs of the direct pathway appear to be relatively spared in the early stages. Because of the great morphological and electrophysiological similariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 82 publications
0
43
0
3
Order By: Relevance
“…119,[248][249][250][251][252] Moreover, SPNs show electrophysiological signs of cortical disconnection in R6/2, Q175, or YAC128 mice at symptomatic ages at which SPNs do not yet show loss. 100,135,136,251,253 The corticostriatal input arises from 2 neuron types, an intratelencephalically projecting (IT) type residing predominantly in layer III and upper layer V, and a pyramidal tract (PT) type located primarily in lower layer V. [254][255][256][257][258][259][260][261][262] We and other investigators have found in rats and monkeys that PT-type corticostriatal neurons preferentially contact striatal neurons projecting to GPe with larger terminals, while IT-type cortical neurons preferentially target striatal neurons projecting to GPi or SNr with smaller terminals (Figure 12). [263][264][265][266] In our study in 12-month-old Q140 mice, the loss of corticostriatal terminals occurred selectively for smaller terminals, suggesting they might be IT-type terminals and preferentially lost from direct pathway type striatal neurons.…”
Section: Abnormalities In Cortical Input To Striatal Projection Neumentioning
confidence: 99%
See 1 more Smart Citation
“…119,[248][249][250][251][252] Moreover, SPNs show electrophysiological signs of cortical disconnection in R6/2, Q175, or YAC128 mice at symptomatic ages at which SPNs do not yet show loss. 100,135,136,251,253 The corticostriatal input arises from 2 neuron types, an intratelencephalically projecting (IT) type residing predominantly in layer III and upper layer V, and a pyramidal tract (PT) type located primarily in lower layer V. [254][255][256][257][258][259][260][261][262] We and other investigators have found in rats and monkeys that PT-type corticostriatal neurons preferentially contact striatal neurons projecting to GPe with larger terminals, while IT-type cortical neurons preferentially target striatal neurons projecting to GPi or SNr with smaller terminals (Figure 12). [263][264][265][266] In our study in 12-month-old Q140 mice, the loss of corticostriatal terminals occurred selectively for smaller terminals, suggesting they might be IT-type terminals and preferentially lost from direct pathway type striatal neurons.…”
Section: Abnormalities In Cortical Input To Striatal Projection Neumentioning
confidence: 99%
“…121,248,251,270,271 The dSPNs in particular show early enhanced and later reduced corticostriatal excitation. 253,270,272 The reduced corticostriatal excitation appears to reflect the loss of corticostriatal input rather than reduced striatal excitability, because dSPNs remain more depolarized at rest and have elevated membrane input resistances. 248,252,273 The preferential loss of cortical input to dSPNs we observed is of interest in light of the possibility that the loss is neuroprotective.…”
Section: The Basis Of the Selective Reduction In Cortical Terminals Omentioning
confidence: 99%
“…41 In fact, a shift in MSN excitability could alter the dynamics of behavior-related neuronal processing throughout basal ganglia circuitry. 42,43 Accordingly, Cayzac et al 44 reported a change in the ability of MSNs to process learning and task-related information in premotor-symptomatic R6/1 mice, another truncated model of HD but with later symptom onset owing to a smaller number (~110) of CAG repeats.…”
Section: Keypointsmentioning
confidence: 99%
“…Huntington's disease is an inherited neurodegenerative disease characterized by a selective loss of MSNs in the striatum. 149,150 Huntington's disease is caused by a mutation in the Huntingtin gene encoding the Huntingtin protein and is characterized by movement disorders (eg, involuntary choreiform movements) and behavioral and cognitive deficits. 37,151 Even though no specific degeneration of the striatal cholinergic interneurons has been described in HD, [152][153][154] studies in HD transgenic mice have reported an abnormally low release of ACh in the striatum, 2,155 pointing out a role of these interneurons in the pathophysiology of the disease.…”
Section: Huntington's Diseasementioning
confidence: 99%